The Influence Of Back Massage On Insomnia Reduction In Elderly At Wisma Asissi Nursing Home In Sukabumi In 2019 - Indrayani, Triana; Liuri, Kunigunda (Journal of Global Research in Public Health, 2020)
Back massage has many benefits for the human body system such as reducing muscle pain in the cardiovascular system, improving blood circulation and stimulating blood flow throughout the body, also stimulating cell regeneration– and its effects on the nervous system is that it can reduce the risk of disruption of sleeping quality in elderly people. This study used Quasi-Experimental with "one group of pretest post-test" design. The number of samples taken in carrying out this study was 20 people – who were chosen using the total sampling technique. The difference in the categories of insomnia before and after being given back massage therapy at Wisma Asisi Nursing Home in Sukabumi, have sleeping quality average in the pretest of as much as 20.20 and an average in the post-test of as much as 70. This shows that the average value of sleeping quality in the post-test has decreased with the value of difference of 3.2. There is an effect of back massage therapy on reducing insomnia in the elderly respondents at Wisma Asisi Nursing Home in Sukabumi, with pretest and post-test of 8.248 with p value of 0.000 (p <0.05)